2013
DOI: 10.1128/jvi.02158-12
|View full text |Cite
|
Sign up to set email alerts
|

Holoendemic Malaria Exposure Is Associated with Altered Epstein-Barr Virus-Specific CD8 + T-Cell Differentiation

Abstract: e Coinfection with Plasmodium falciparum malaria and Epstein-Barr virus (EBV) is a major risk factor for endemic Burkitt lymphoma (eBL), still one of the most prevalent pediatric cancers in equatorial Africa. Although malaria infection has been associated with immunosuppression, the precise mechanisms that contribute to EBV-associated lymphomagenesis remain unclear. In this study, we used polychromatic flow cytometry to characterize CD8 ؉ T-cell subsets specific for EBV-derived lytic (BMFL1 and BRLF1) and late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…+ population of b-cell-specific CD8 T cells in type 1 diabetic patients that was significantly less frequent in healthy control subjects, again consistent with an antigen-driven disease process as reported previously in a viral system (43). Importantly, all three analytical approaches yielded significant differences between subject groups solely within the b-cell-specific CD8 T cell compartment.…”
Section: Discussionsupporting
confidence: 87%
“…+ population of b-cell-specific CD8 T cells in type 1 diabetic patients that was significantly less frequent in healthy control subjects, again consistent with an antigen-driven disease process as reported previously in a viral system (43). Importantly, all three analytical approaches yielded significant differences between subject groups solely within the b-cell-specific CD8 T cell compartment.…”
Section: Discussionsupporting
confidence: 87%
“…Studies of children in high-and lowincidence malaria areas show the former have high EBV viral loads (Moormann et al 2005). Subsequent studies have shown that children living in endemic malarial areas have reduced CD8 T-cell responses to EBV lytic and latent antigens (Moormann et al 2007) or phenotypic changes in these responses consistent with greater differentiation (Chattopadhyay et al 2013); each could conceivably alter the virus-host balance to favour the development of Burkitt lymphoma. An alterative, but not necessarily mutually exclusive explanation for the development of Burkitt lymphoma is that the tumours are able to develop because they escape immune control.…”
Section: T-cell Responses In Patients With Ebv-associated Malignancymentioning
confidence: 98%
“…In addition, non-BL, malaria-exposed children lacking IFN-γ responses to EBNA-1 had higher median EBV loads compared to healthy children with EBNA1-specific T-cell immunity. Another study by Chattopadhyay et al used HLA-A2 tetramers to phenotype CD8+ T cells specific to EBV lytic (BMFL1 and BRLF1) and latent (LMP1, LMP2, and EBNA3C) peptides and multidimensional analysis of CD45RO, CD27, CCR7, CD127, CD57, and PD-1 expression (Chattopadhyay et al 2013). They found that CD8+ T cells against lytic antigens tended to display an exhausted phenotype lacking homeostatic potential and individuals residing in malaria holoendemic areas had more differentiated CD8+ T cells to EBV latent antigens with fewer central memory subsets compared to those living in regions with little to no malaria transmission.…”
Section: Ebv-specific T-cell Immunosurveillancementioning
confidence: 99%